In the Holocene - Ribas, João; MIT List Visual Arts Center (Berlin : Sternberg Press, 2014)
In the Holocene' is based on a 2012 group exhibition of the same name at the MIT List Visual Arts Center that explored art as a speculative science, investigating principles more commonly associated with scientific or mathematical thought. Through the work of an intergenerational group of artists, the exhibition and book propose that art acts as an investigative and experimental form of inquiry, addressing or amending what is explained through traditional scientific or mathematical means.
"Published on the occasion of the exhibition In the Holocene at the MIT List Visual Arts Center, October 19, 2012-January 6, 2013, curated by João Ribas"--Title page verso.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: MIT List Visual Arts Center -- Exhibitions; MIT List Visual Arts Center